Analisis Indeks Kebutuhan Lahan dan Biaya dari Perencanaan IPAL Terpadu di Kawasan Aerocity X - Adryan Lukman Indira; Didin Agustian Permadi; Etih Hartati (Jurnal Serambi Engineering, 2021)
District Aerocity X in Kabupaten Majalengka is a commercial  and industrial area that enhances  economic growth in Provinsi Jawa Barat. The district with an area of 3,480 ha is integrated into  the domestic sector. However, this area  also has the potential  to cause harm  if the waste is not treated.  Following PP No 142 Tahun 2015,  each industrial area  must provide an effective and efficient wastewater treatment plant (WWTP). This design  plan begins with the  analysis  of issues  on the study site . The data were obtained using the Aerocity X District Pre-Development Office  study method .  The method of  designing effective alternatives for WWTP used the weighted ranking technique (WRT), each alternative was compared with two fundamental,  technical and non-technical aspects. The purpose of this design plan is to analyze the index of land and cost requirements for WWTP. The yield of wastewater was 3.99 m3/s. The most effective land and the cost is complete mix-activated sludge. The result of installing  the design plan requires an area of 9,446.5 m2/m3 of wastewater and a cost of Rp5,619.53x106/m3 of wastewater.